Controverses et convergences. L’Autofictif d’Éric Chevillard - Maziarczyk, Anna (Romanica Silesiana)
Currently one of the most controversial writers, Éric Chevillard shapes the foundations and the raison d’être of his apparently ludic aesthetics in a polemic and creative dialogue with the literary tradition. Experimenting in his subsequent texts with narrative forms that subvert generic boundaries and conventional stylistics, he exploits in L’Autofictif the new possibilities offered by the digital revolution. Kept on the web since 2007, his literary notebook has also been published as a book, thus becoming a multimodal project, which perfectly fits the contemporary culture of convergence, based on the interplay between the old and the new media. Playing with the media, Chevillard again proves his anticonformist attitude to conventional patterns and refuses to succumb to the prevailing trends. By situating literature at the borderline between high and mass cultures, he endows it with a new shape in the times, when it is commonly assumed to be doomed to oblivion. Key words: Literary blog, culture of convergence, narrative experiments, ludic aesthetics.